(3GdQjGVjGJ GdGbJUGOjI (B:s (3CSS h JWHjbGJ (B/s - (3cGXe, cGed YdGhjs; (3dGaj eQRhc, YGWa s ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2010)
(3GdCSS GdYGeI, LHQ GdeUahaGJ h JWHjbGJgG aj GdGbJUGO, GdeTJbGJ h GdJcGed h JWHjbGJgG GdGbJUGOjI, GdHQeLI GdNWjI, JMdjd GdeSJNOe GdefJL, eYGOdGJ GdaQhb h JWHjbGJgG GdGbJUGOjIs
(3HHdjhZQGajG(B: (3U(B.225-226s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdJMdjd GdQjGVj(B- (3GdEbJUGOs; (3GdQjGVjGJs